EFFECT OF METHANOLIC EXTRACTS FROM THE LEAVES OF TULSI (OCIMUM SANCTUM) ON THE OVARY OF GONOCEPHALUM BRACHYELYTRA (KASZAB), (COLEOPTERA: TENEBRIONIDAE) - SANTESHWARI, (The Bioscan, 2012)
In Gonocephalum brachyelytra (Kaszab), a pair of about 3.64mm long and white ovary is found. Each ovary is composed of twenty eight to thirty eight numbers of ovarioles. The ovarioles are clearly differentiated into terminal filament, germarium and vitellarium. The germarium possesses four to five developing oocytes and trpohocytes which provide nourishment to the developing oocytes. The vitellarium possesses developing oocyte, maturing oocyte and large yolky globules i.e. resorptive oocyte. In the control ovary each ovariole shows normal release of oogonial cells after maturation. Whereas, the insect’s ovariole treated with the methanolic tulsi extract releases less amount of oogonial cells. Increase in intercellular spaces observed between the trophocytes. The trophocytes shows their contracting nature. The yolky materials of oocyte show distortion. Clumping of mature oocyte also shows sign of decrease in oogenesis. The intercellular spaces provide pathway for protein to enter into the cytoplasmic area, but not into the nuclear region. It checks the active protein deposition and decrease the process of mitosis and meiosis. As a result prevention in the phenomenon of oviposition is observed. In the present study the extract of tulsi shows antioogenetic activity.